2022
DOI: 10.3390/ijerph191912908
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating the Co-Creation Method into Social Innovation Design to Promote Intergenerational Integration: A Case Study of a Public Square

Abstract: With the COVID-19 pandemic sweeping the world, there is an increased focus on intergenerational relationships, community mental health issues, and well-being in community contexts. This paper assesses the effectiveness of a co-creation approach for intergenerational integration at the theoretical level. The study used a collaborative co-creation design method in the community design process to explore whether the participation of community residents of all ages in addressing community issues promoted communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The participants were then asked to think freely about the future kitchen design without interrupting each other, allowing for creativity and imagination. This differs from previous studies of co-design, which have tended to involve direct multi-stakeholder co-discussion and design, resulting in the restriction of individual ideas and insufficient expression [ 48 , 50 , 61 ]. The expression of individual innovation is the basis of co-design and provides individual materials for a creative co-design pool, which is indispensable.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The participants were then asked to think freely about the future kitchen design without interrupting each other, allowing for creativity and imagination. This differs from previous studies of co-design, which have tended to involve direct multi-stakeholder co-discussion and design, resulting in the restriction of individual ideas and insufficient expression [ 48 , 50 , 61 ]. The expression of individual innovation is the basis of co-design and provides individual materials for a creative co-design pool, which is indispensable.…”
Section: Discussionmentioning
confidence: 68%
“…Co-design has also been applied in areas such as urban development planning and public space design to increase the fit with human needs and behavioral patterns [ 49 ]. For example, Wu et al (2022) used co-creative design approaches in the community design process to promote intergenerational integration [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, through our research practices, we concluded that the core of intergenerational integration lies in effective communication between intergenerational groups, equal collaboration, and strong empathy. This also shows that, through co-creation interventions, people are empowered to feel respected and gradually move from being served to being active contributors to the community [ 76 ]. We achieved this by incorporating the core conceptual thrusts of community psychology and also found that a collaborative co-creation approach effectively promoted intergenerational cognition, improved intergroup relations, and positively influenced community residents’ mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Value co-creation activities are the relationships that create value between businesses and customers, allowing clients to participate in developing ideas for products and services to match the market context (Prahalad & Ramaswamy, 2004;Wu et al, 2022). The value co-creation process is where enterprises work in cooperation with all stakeholders (Hale et al, 2013;Popp et al, 2021).…”
Section: Literature Review Value Co-creation Activities Of Studentsmentioning
confidence: 99%
“…Second, Ngoc and Huy (2016) promote decision-making collaboration in the learning process, which allows students and lecturers to work together to refine the student experiences (Ngoc & Huy, 2016). Third, they promote organizational innovation, which has significantly positively impacted their performances (Phan, 2019;Popp et al, 2021;Wu et al, 2022).…”
Section: Literature Review Value Co-creation Activities Of Studentsmentioning
confidence: 99%